Bedside Procedures for the Intensivist - Frankel, Heidi L.; deBoisblanc, Bennett P. (Springer New York : Imprint: Springer, 2010)
Bedside Procedures for the Intensivist delivers practical tips and clear, step-by-step instruction on the most common procedures in the ICU. The convenient and portable handbook focuses on ultrasound-guided techniques, including an introduction to ultrasound physics and principles, while individual chapters provide concise "how-to" text supplemented with numerous full-color figures and tables that summarize key content. Residents, fellows, and trainees in critical care will benefit from the detailing of indications and contraindications for performing core procedures, while more experienced intensivists will find the book a reliable source of review material. Key procedures described include: • Ultrasound-guided vascular access • Ultrasound-guided drainage • Focused echocardiography • Airway management • Dialysis and apheresis • Pericardiocentesis • Insertion of vena cava filters • Percutaneous dilational tracheostomy • Open tracheostomy • Transbronchial biopsy • Percutaneous endoscopic gastrostomy • Intracranial monitoring.